Pengaruh Penggunaan Online Shop, Promosi Digital, Gaya Hidup dan Self Control terhadap Perilaku Konsumtif: Studi Kasus Civitas Akademika FEBI, UIN STS JAMBI - Rahma Dwi Frasansyah; Elyanti Rosmanidar; Neneng Sudharyati (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
Consumptive behavior is the activity of spending one's finances based on desires without thinking about needs and not accompanied by logical decision making. Consumptive behavior is commonplace among students and staff at a university, they always follow current trends and make purchases because of attractive promotions. The aim of this research is to find out the influence of the use of online shops, digital promotions, lifestyle and self-control on the consumer behavior of the FEBI UIN Jambi Academic Community. This research was carried out using a quantitative descriptive approach and carried out direct observations in the field, as well as using the SPSS 29 tool. The results of this research were that there was no significant influence on the variables of online shop use and self-control on consumer behavior because the results obtained were 0.340 > 0.05 and 0.728 > 0.05, but in the digital promotion and lifestyle variables there is a significant influence on consumer behavior because the results obtained are 0.001 > 0.05. And a simultaneous influence was found between the variables of online shop use, digital promotions, lifestyle and self-control on consumer behavior. And there is a joint influence of the variables of online shop use, digital promotions, lifestyle and self-control on consumer behavior. And the influence of variables X1 (Use of Online Shop), X2 (digital promotion), X3 (lifestyle) and This